Collaborative Governance and its Role in Fighting the Pandemic: From the Conception of what it is to the Verification of its Inexistence (Global Journal of Human-Social Science, 2020)
Complex problems such as the public management of a pandemic require coordinated and horizontal action, involving not only public officials and their state agents but also representatives of civil society, their universities, and researchers, the technical and the corporate staff in the health field, such as collaborative governance practices. However, what we observed in Brazil in the Covid-19 first months of the pandemic, was the intensified action in the government sphere, with precarious effectiveness and little coordinative efficiency.
Keywords: public management collaborative governance territorial governance covid-19 pandemic